Diversity analysis and structural modeling for some traits in wheat genotypes - Saleh, Maysoun M.; Kenaan, Rajaa; Suliman, Zaeda Alsayd; Ali, Walid A.; Jabbour, Yaman (Journal of Phytology, 2021)
This investigation was carried out during 2018/2019 season in three locations Homs, Al-Swaida and Tartous belongs to the General Commission for Scientific Agricultural Research in Syria, using 17 Italian, Syrian and Ethiopian wheat genotypes to estimate the potential diversity by principle component and cluster analysis, and to study the structural modeling between grain yield and other traits to define best traits as predictors and selection indexes of grain yield, and to determine the superior genotypes in grain yield. Results indicated a remarkable variation of 74% due only to the first four principle components with Eigen value > 1. PC Biplot showed that Tartous was the best location, and the genotype SD09 was superior in grain yield per plant followed by SH5 and IP39. Structural modeling results revealed that the total and fertile tillers number per plant were the best predictors for grain yield per plant, while fertile tillers per plant with grain weight per spike could be used as selection indexes of wheat grain yield because they had positive strong direct effect on grain yield per plant. Cluster analysis results confirmed the need to assess more various genotypes from different origins.